Kaschnitz, Enzensberger, and Sandig: The Ecopoetics of Water Pollution - Charlotte Melin (Studies in 20th & 21st Century Literature, 2016)
This ecocritical reading of Marie Luise Kaschnitz’s poetic cycle “Rückkehr nach Frankfurt” ‘Return to Frankfurt’ (1945/46), Hans Magnus Enzensberger’s epic poem Der Untergang der Titanic ‘The Sinking of the Titanic’ (1978), and a 21st-century poem by Ulrike Almut Sandig analyzes key shifts in poetic representations of water pollution. The essay explores underlying cultural and political attitudes about water that define literary depictions of its pollution. It argues that these texts register a conceptual turn away from aesthetic appreciation of water in terms of its culturally rich, purifying properties and toward scientific understanding that emphasizes the social and legal dimensions of water pollution. Ecocritical interpretation of such works, thus, enables deeper understanding of ongoing transformations in the lyric genre. The concluding interpretation of Sandig’s text points to the increasing presence of unnatural elements in representations of the environment as symptomatic of broader literary changes. It argues that developments in German nature poetry since 1945 have increasingly led poets to experiment with expressive possibilities for lyric poetry that foreground cathartic responses to human and environmental history.
Keywords: German poetry; ecocriticism; water